Trauma on Human Skeletons: A Study on Cause of Death Related with Trauma - Çeker, Deren; Deniz, İdris; Sevim, Ayla (The Bulletin of Legal Medicine, 2019)
Objective:In forensic anthropology, skeletal trauma analysis is conducted to determine the patterns of trauma in violent deaths. Bone fractures, cut marks and other defects observed on the human bones are analyzed in order to determine the manner and the possiblecause of death. The aim of this study was to examine bone fracturing patterns of the victims, utilizing CT scans so as to diagnose the relationship between bone fracture and mortality. It also tested the accuracy and reliability of the perimortem trauma determinations in the forensic anthropological results.Materials and Methods: The sample of this study consists of 30 cases of forensic significance, and includes 23 male and 7 female individuals who died from traumatic injuries between 20.02.2016 and 29.11.2017. The victims died from traffic accidents, fall from height, hanging and firearm. Gravely injured individuals underwent CT scanning in the national hospital prior to death except for one individual and bone fractures were located by using a 3D medical imaging program.Results:1580 bones were analyzed and 242 bone fractures were located, independent to the autopsy findings. The results of the study indicated that 28 individuals died from blunt trauma and 2 individuals from gunshot trauma, the number of deaths for men was greater than for females, the highest mortality age range was between 21 and 30 years old and fatal bone fractures were mostly located on the head and chest.Conclusion:Forensic anthropological analysis results were found to have a success rate of 90% (n=30/27) in determining the trauma type and ...
Keywords: Forensic Sciences; Forensic Anthropology; Skeleton; Perimortem; Trauma; Cause of Death